Driving User Satisfaction and Purchase Intention of Mobile Health Applications: Evidence from Indonesian Hospitals - Angelica Shania Dani Putra Benjamin; Novika Candra Astuti (Jurnal EMT KITA, 2026)
Digital transformation in the Indonesian healthcare sector is progressing rapidly, but hospital app usage lags behind the health aggregator platforms. This study aims to analyze the factors influencing user satisfaction and its impact on continuance intention and purchase intention for Medical Check-Up (MCU) services. By integrating the UTAUT and DeLone & McLean IS Success models, data was collected from 206 respondents who used the MySiloam and MIKA apps in the Greater Jakarta area, and was analyzed using the PLS-SEM method. The results show that information quality, ease of use, service quality, and social influence are significant predictors of user satisfaction. Conversely, technical aspects such as system quality and facility conditions did not have a significant effect, indicating a hygiene factor phenomenon. User satisfaction proved to be a crucial full mediator in driving continuance intention and purchase intention. Continuance intention also acts as mediator for satisfaction to influence purchase intention. For managerial implications, hospitals are advised to reorient investments from technical infrastructure to strengthening medical content, ease of use, and service responsiveness to create a satisfaction-centered patient experience for long-term business sustainability.